Chromatin Targeting of HIPK2 Leads to Acetylation-Dependent Chromatin Decondensation - Haas, Jana; Bloesel, Daniel; Bacher, Susanne; Kracht, Michael; Schmitz, M. Lienhard (Frontiers in Cell and Developmental Biology, 2020)
The protein kinase homeodomain-interacting protein kinase 2 (HIPK2) plays an important role in development and in the response to external cues. The kinase associates with an exceptionally large number of different transcription factors and chromatin regulatory proteins to direct distinct gene expression programs. In order to investigate the function of HIPK2 for chromatin compaction, HIPK2 was fused to the DNA-binding domains of Gal4 or LacI, thus allowing its specific targeting to binding sites for these transcription factors that were integrated in specific chromosome loci. Tethering of HIPK2 resulted in strong decompaction of euchromatic and heterochromatic areas. HIPK2-mediated heterochromatin decondensation started already 4 h after its chromatin association and required the functionality of its SUMO-interacting motif. This process was paralleled by disappearance of the repressive H3K27me3 chromatin mark, recruitment of the acetyltransferases CBP and p300 and increased histone acetylation at H3K18 and H4K5. HIPK2-mediated chromatin decompaction was strongly inhibited in the presence of a CBP/p300 inhibitor and completely blocked by the BET inhibitor JQ1, consistent with a causative role of acetylations for this process. Chromatin tethering of HIPK2 had only a minor effect on basal transcription, while it strongly boosted estrogen-triggered gene expression by acting as a transcriptional cofactor.